The Role of Compensation Moderation on the Effect of work Environment on Employee Loyalty at PT. Prima Karya Manunggal - Ilham Safar; Mujahid; Ramalwati; Muwaffiq Nurimansyah Mapparenta; Nasyirah Nurdin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Employee loyalty is a picture of healthy and competent organizational management. Loyalty becomes an essential aspect in improving organizational performance and achieving goals. This study explains the influence of the work environment, which is divided into two points, namely the physical and non-physical work environment, on employee loyalty by making the compensation variable a moderating variable. The number of respondents in this study was 135 people. Data analysis used SmartPLS software by looking at moderated regression analysis (MRA) in answering the hypotheses that were built. The results of the study show that the physical and non-physical work environment has a significant influence on employee loyalty. At the same time, the compensation variable cannot moderate the relationship between the impacts of the physical work environment on loyalty. Still, on the contrary, compensation can negotiate the influence of the non-physical work environment on loyalty. Employee.